Раскопки поселения в Барабановской балке в 2009 г. - Храпунов, И.Н.; Власов, В.П. (Археологічні дослідження в Україні, 2010)
A settlement in Barabanivska gully is situated 25 km to the south-east from Simferopol. In 2009, an excavation area covered five squares of 5 × 5 m size. Artificial terraces, stone buildings, cob floors, and husbandry pits were uncovered. The main groups of finds from the cultural layers are the following: fragments of light-clay and red-clay amphorae, handmade pottery and burnt clay-braziers. The settlement belongs to Late Scythian culture and is dated within the period from the 2nd to the 4th c. AD.